The Influence of Liquid Tanks on the Seismic Response of Isolated Structure - MIRZADA, RAMEEN (İstanbul Kültür Üniversitesi, 2022)
This study investigates the influence of liquid tanks on the seismic response of a Lead Rubber Bearing isolated structure under six near-fault ground excitations. Liquid tanks with various sizes and aspect ratios located on the base floor were used to assess the effect of sloshing on the seismic response. The response history analysis of the building model was performed with a MATLAB script. The sloshing effect of liquid was considered by using a mechanical modeling of liquid tanks with rigid walls. The structural response was analyzed using the selected ground acceleration records. The response parameters, such as hysteresis loops, bearing displacement, story drift of the structure, and liquid sloshing displacements, were investigated. The analysis results show that large bearing displacements were observed for building models with slender tanks subjected to earthquakes with high Peak Ground Displacements (PGD).
Sıvı Tankların İzolasyonlu Yapıların Sismik Tepkisi Üzerindeki Etkisi
▪ Yüksek lisans tezi.
Keywords: Liquid Tanks; Seismic Isolation; Lead Rubber Bearing; Response History Analysis; Hysteresis loops; Bearing Displacement